Vegetative growth control in European pear trees through physical and chemical methods - Luz, Alberto Ramos; Souza, Deivid Silva de; Petineli, Rafael; Hipólito, Joaseane de Souza; Rufato, Leo; Kretzschmar, Aike Anneliese (Revista de Ciências Agroveterinárias, 2018)
The various failed attempts to produce pears in Brazil are driven by high consumption, which presents a growing scenario of imports to attend to the consumers demand. In 2015, 179 thousand tons of pears were imported, most from Argentina and Portugal. The limitation of pear cultivation has not been due to lack of market, but due to several factors, such as low fruit set, insufficient formation of production structures and excessive vegetative growth. The objective of this work was to evaluate the vegetative growth and fruit set of European pear trees submitted to different growth control techniques. The experiment was conducted during 2012/2013 and 2013/2014 season in a commercial pear orchard located in Vacaria city, Rio Grande do Sul State, at 971 m altitude. Packham’s Triumph, William’s, Red Bartlett, Abate Fetel and Carrick, all grafted on Pyrus calleryana, were submitted to treatments of simple girdling, double girdling, single trunk cutting, double trunk cutting and application of the Trinexapac-ethyl plant growth regulator (1600 mg L-1). According to the results, it was possible to observe that there was a reduction of vegetative growth only in the Packham’s cultivar submitted to double girdling, single trunk cutting and Trinexapac-ethyl. The use of the trunk cutting and girdling technique increases the flowering return and also the productivity of ‘Abate Fetel’ and ‘Carrick’ pear trees, and the Trinexapac-ethyl decreases the return bloom of ‘Abate Fetel’ and ‘Carrick’ pear trees in the studied conditions.